PENYIARAN BERITAKRIMINAL DALAM KERANGKA PERLINDUNGAN HAK TERSANGKA/TERDAKWA - Ig Punia Atmaja Nr (Yuridika, 2017)
Broadcasting of criminal news on television constitutes part of freedom of the press to provide information for the public through the print media or electronic media. Broadcasting of criminal news through television describes events of crime as if we directly see from the crime scene. There have been regulation and institution providing for and overseeing broadcasting, namely Law Number 40 Year 1999 regarding the Press and Law Number 32 Year 2002 regarding Broadcasting, the Press Council stipulating “journalists’ code of ethics” and the Indonesian Broadcasting Commission stipulating “Broadcast program standards and broadcasting code of conduct”. The presentation of criminal news by showing the faces and identities of suspects or defendants constitutes a violation of the principles of presumption of innocence, namely someone must be deemed or treated not guilty until there is a court ruling stating that he or she is guilty. In addition, the broadcasting of criminal news affects suspects or defendants in obtaining due process of law, public prosecutors and judges who examine the case. Therefore, it is necessary that the broadcasting of criminal news not violating code of ethics or rules and the rights of suspect or defendant be endeavored.